OVER-THE-COUNTER MULTIVITAMIN TRANSCUTANEOUS PATCH DOES NOT CORRECT NUTRITIONAL DEFICIENCIES IN PATIENTS UNDERGOING BARIATRIC SURGERY: A CASE REPORT - Vasanthakumar, Vijaykiran Pasupulati; Vietor, Nicole; Shakir, Mohamed; Hoang, Thanh (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Nutritional deficiencies of water-soluble vitamins are commonly seen following bariatric surgery and proper replacement is critical. The availability of over-the-counter (OTC) vitamin supplements has created challenges in appropriate vitamin replacement, given the potential for lower efficacy than typical prescription-strength formulations. We report a patient who developed lower extremity neuropathy following Roux-en-Y gastric bypass surgery (RYGB) despite using OTC skin patch multivitamins. CASE A 62-year-old female underwent RYGB for obesity and had an uneventful immediate postoperative course. She returned for follow-up 6 months later complaining of severe, recurrent vomiting along with lower extremity weakness, paresthesia, dizziness and ataxia. She reported sharp pain and numbness over bilateral anterior thighs. Medication review revealed an OTC multivitamin patch that she was taking to correct any vitamin deficiencies. Her BP was 101/62 mm Hg, HR was 60 bpm, BMI was 26.41, examination of heart, lungs and abdomen were normal. Neurological examination showed decreased sensation to touch on both feet, legs and 4/5 muscle strength on bilateral lower extremities. Laboratory examinations showed normal CBC, normal liver function, serum zinc 55 mcg/dL (ref 56- 134), copper 115 mcg/dL (ref 72-166), vitamin B1 38.1 nmol/L (ref 66.5 – 200), vitamin B12 323 pg/mL (232-1245 pg/mL), 25-hydroxyvitamin-D 29 ng/mL (30-100 ng/mL). Cervical and thoracic MRI imaging were normal. After stopping the vitamin patch, she was treated with intravenous thiamine followed by 100 mg oral thiamine TID along with 1000 mcg oral cyanocobalamin once daily. She experienced complete recovery of her symptoms in 6 weeks. CONCLUSION Our patient relied on an OTC multivitamin patch which proved to be ineffective since it only contained 1 mg and the usual recommended dose is 50-100 mg orally daily. Symptoms will usually resolve with proper treatment. It is essential to pay attention to the nutritional status of post- bariatric surgery patients.